Basic researchAssociation of glutathione-S-transferase P1 genotypes with susceptibility to bronchial asthma in children - Abdel-Alim, Sherif M.; El-Masry, Manal M.; Aziz, Mona; El-Bassiony, Soheir O.; Aly, Azza A. (Archives of Medical Science, 2007)
Introduction: Asthma is characterized by airway inflammation, a critical component of which is oxidative stress. We describe an association study designed to examine whether allelic variation at the glutathione-S-transferase GSTP1 locus influences expression of asthma. Material and methods: Fifty asthmatic children, thirty-five atopic and fifteen nonatopic, with forty healthy controls were enrolled in the study. All participants were subjected to complete blood count, total serum IgE, skin prick testing and peak expiratory flow rate. Polymerase chain reaction-based assays were performed to determine GSTP1 genotypes among asthmatic and healthy control subjects. We explored whether the GSTP1 substitutions influence susceptibility to asthma and its phenotypes. Results: Among the 90 cases, 43 cases (47.8%) had GSTP1 genotype BB, 39 cases (43.3%) had GSTP1 genotype AA, 6 cases (6.7%) had GSTP1 genotype AB, and 2 cases (2.2%) had GSTP1 genotype AD. We found no significant differences in mean values of total serum IgE and skin test positivity among different genotypes. The PEFR% predicted of the BB genotype was significantly higher than that of both AA and AB genotypes (p<0.001), with no significant differences between the latter two genotypes. The frequency of GSTP1 AA was increased significantly in the asthmatic cases (76.9%) compared to controls (23.1%), with p value <0.001. However, the frequency of GSTP1 BB was decreased in the asthmatics (32.6%) compared to controls (67.4%), with p value <0.1. Conclusions: The results of the present study suggest that GSTP1 BB conferred almost a threefold lower risk of asthma than did GSTP1 AA.